2016
DOI: 10.1103/physrevfluids.1.083701
|View full text |Cite
|
Sign up to set email alerts
|

Convection-driven kinematic dynamos at low Rossby and magnetic Prandtl numbers

Abstract: Most large-scale planetary magnetic fields are thought to be driven by low Rossby number convection of a low magnetic Prandtl number fluid. Here kinematic dynamo action is investigated with an asymptotic, rapidly rotating dynamo model for the plane layer geometry that is intrinsically low magnetic Prandtl number. The thermal Prandtl number and Rayleigh number are varied to illustrate fundamental changes in flow regime, ranging from laminar cellular convection to geostrophic turbulence in which an inverse energ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 63 publications
3
20
0
Order By: Relevance
“…The DNS flow field analyses support the idea of a fully self-consistent dynamo in the oscillatory regime, as has also been proposed by Calkins et al. (2015, 2016 b ); Davidson & Ranjan (2018). Helicity is an important ingredient in many dynamo systems (e.g.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The DNS flow field analyses support the idea of a fully self-consistent dynamo in the oscillatory regime, as has also been proposed by Calkins et al. (2015, 2016 b ); Davidson & Ranjan (2018). Helicity is an important ingredient in many dynamo systems (e.g.…”
Section: Resultssupporting
confidence: 85%
“…Rapidly rotating, kinematic plane layer dynamo models have now demonstrated that low oscillatory convective modes are actually capable of generating dynamo action at lower and in lower electrical conductivity fluids than in moderate cases (Calkins et al. 2016 a , b ).…”
Section: Introductionmentioning
confidence: 99%
“…Moffatt 1978). For sufficiently long simulation times, it is expected, and observed by Calkins et al (2016b), that α ij will become symmetric; it was further observed that α 12 ≈ α 21 ≈ 0 as t → ∞.…”
Section: )mentioning
confidence: 79%
“…However, rapid rotation alone is sufficient for generating large-scale magnetic fields [13], even for laminar, small-Reynolds-number flows that lack an inverse cascade [14][15][16]. In the asymptotic limit of rapid rotation, LSVs are unimportant for the onset of dynamo action [16]. However, the influence of magnetic field on the inverse cascade remains poorly understood due, in large part, to the limited parameter range of previous DNS studies.…”
mentioning
confidence: 99%